Incidencia de anemia en embarazadas adolescentes y factores de riesgo del Centro de Salud Santa Rosa, Quevedo, 2014 - Giacometti Rosero, Zaida Mercedes (2015)
The anemia of the adolescent mother is a problem of public health for the mother as for its son, the anemia is considered to be a low concentration of hemoglobin accompanied by a reduction of the value hematocrito, especially in others gestantes and with major elevancyin adolescent women, increasing the risks of premature child bearings, under weight on having been bom and major risks of bled to the moment the childbearing accomparied by inadequate diet and the consume of iron more acidic folico as preventive measurement or o treatment for the anemia in case of being detected. The intention of the investigation was to determine the anemia incidence in pregnancy women, who assist to the health center Santa Rosa and to know is factors of risks to which the adolescents are predisposed. For which information is compiled to the personnel that attends to the adolescents, to know like this one prepared to tackle the topic of the anemia in the stated group, and to know the factor of risks of the pregnant woman, which it is its incidence and in what grade it can affect its state and that of the child. With the stated premises one proceded to the collection of information, of the case histories, knowing its hemoglobin level and hematocrio to be able to determine if anemia exist or not. It was are retrospective, descriptive study of not invasive transverse type. The most predominant results allowed to know the anemia incidence in the group in study which presented 23% of incidence of anemia or new cases at the moment of being registered in the health center with is respective examination. Between other risk factors we have that the age that more presented anemia went in the group from of 12 years to 14 years, accompanied on the nutritional state of weight with 26%. Key Words: Anemia ferropenica, pregnant adolescent, factors of risks, incidence.